Factor that lead towards stress among police case study: district police headquarters Bandar Baharu, Kedah. / Nur Nadrah Najihah Mohd Nazari and Nursyahirah Zainal - Mohd Nazari, Nur Nadrah Najihah; Zainal, Nursyahirah (2018)
In the article of (Muhammad Jehangir, 2011 ), stress has been a topic of interest to the researchers since the Second World War (Newton 1995). Recently, stress had been global issue that faced by individual and the organization. This issues must be taken serious attention all over the world. The organization are finally waking up to the fact that a lot of human potential are being drained away due to stress (Muhammad Jehangir, 2011 ). In 2001, according to article of (Farah Syazreena Azmi, 2016), based on the (Jeremy, Patricia, Mary ,2001) said that they have develop a theory of stress which consists of job-related stress of organizational aspects. Sisk (1977) defined stress as a state of strain, tension or pressure and it is a normal reaction resulting from interaction between the individual and the environment (Oximoso, 2017). Strain means to make great demand on something as tension is a mental or emotional strain that makes natural relaxed behaviour cannot be done by the person who develope stress. In addition, based Oboegbulem (1995),stress is a feeling which occurs when an individual's working or living conditions or circumstances make demands beyond his capacity to handle such a situation physically or emotionally. When a person is faced with disturbing situations, a change in his normal behaviour is usually noticeable. Such an individual may be faced with emotional, cognitive and physiological disruption or malfunctioning which can disorganise and adversely affect his powers of reasoning (Holdsworth & Pharm, 2004).